2020
DOI: 10.1002/hrm.22007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of offering flexible work practices to employees with unpaid caregiving responsibilities for elderly or disabled family members

Abstract: Approximately one in 10 employees in Australia, the United States, and Europe have unpaid caregiving responsibilities for elderly or disabled family members. This combination of employment and caregiving roles is problematic when there is conflict between their simultaneous demands. Flexible work practices can be an important mechanism for assisting these employees. However, limited attention has been given to determining the benefits of flexible work practices for these employees, or the process by which thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…In this study, several social needs were identified: relatedness with supervisor and colleagues, workplace policies, job autonomy and interestingness of job tasks. In other words, organisations can formulate tailor-made workplace policies to fulfil the feasible and reasonable requirements of workers so that workers can flexibly manage the work–life interface [ 109 , 110 , 111 , 112 ]. One notable factor of significance is the attitudes and behaviours of supervisors towards workers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, several social needs were identified: relatedness with supervisor and colleagues, workplace policies, job autonomy and interestingness of job tasks. In other words, organisations can formulate tailor-made workplace policies to fulfil the feasible and reasonable requirements of workers so that workers can flexibly manage the work–life interface [ 109 , 110 , 111 , 112 ]. One notable factor of significance is the attitudes and behaviours of supervisors towards workers.…”
Section: Discussionmentioning
confidence: 99%
“…flexible hours). More flexible work practices increase the likelihood of a person being able to combine caregiving and paid employment (Bainbridge & Townsend, 2020; Longacre et al, 2021; Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As the country context influences outcomes differently (Chung and van der Lippe 2018), organisations should align context with work‐life policies for positive employee outcomes. Australian organisations are facing the challenges of managing a diverse workforce, and flexible working is one of the key incentives to attract new talent and harness the skills and experience of existing employees (Australian Bureau of Statistics 2009; Bainbridge and Townsend 2020). Moreover, as the Australian Government has emphasised increasing female participation rates at the national level (WGEA 2019), the understanding of workplace stigma mechanisms will help organisations to further develop their flexible work policies to accommodate more female employees.…”
Section: Discussionmentioning
confidence: 99%